Awareness of Post-Operative Patients Regarding Informed Consent Form in Public Tertiary Care Hospital of Peshawar Khyber Pakhtunkhwa: A Cross Sectional Survey: Awareness of Patients Regarding Consent Form - Ali Shah, Bakhtyar; Anwar, Muhammad; Begum, Nusrat; Akhtar, Naheed; Sultan, Amir; Tariq, Muzamil; Bibi, Sumaira (Pakistan Journal of Health Sciences, 2023)
The informed consent form is one of the components of bioethics. Written consent from the patient must be obtained prior to any medical or surgical procedure to give the patient freedom of choice. This factor has always been neglected when caring for patients in most third world countries. Objective: To assess postoperative patient awareness of informed consent at Peshawar KP Tertiary Public Hospital (HMC). Methods: This study was conducted from April 2021 to August 2021 at Hayatabad Medical Complex, a tertiary care public hospital in Peshawar. A total sample of 70 patients was drawn by consecutive selection. An adopted and pre-tested questionnaire was used for data collection. Questions were filled in by having the patient understand the question and receiving the answer from the patient. Results: The majority (59%) of the patients included in this study were male, while the mean age was 35 years and the majority of the patients (44%) were illiterate. Awareness of variables (2–7) was 60%, 47%, 30%, 47%, 69%, and 53%, respectively, while awareness levels from questions 8–12 were 59%, 47%, 82%, 40%, and 60%, respectively. Conclusions: The results of the current study indicate that the perception of informed consent among patients in tertiary care public hospitals is reasonably satisfactory, although some lack of participant knowledge of key issues has been identified and needs to be improved through education and awareness.